Absence of Age‐Related Trends in Stable Oxygen Isotope Ratios From Oak Tree Rings. Issue 7 (17th July 2019) - Duffy, Josie E.; McCarroll, Danny; Loader, Neil J.; Young, Giles H. F.; Davies, Darren; Miles, Daniel; Bronk Ramsey, Christopher
Abstract: The potential for age‐related trends in the stable oxygen isotope ratios of latewood alpha cellulose was investigated in samples of living oak trees and historic building timbers from the UK. When the series are examined individually, it is clear that the strongest trends in individual trees and timbers reflect concurrent trends in climate. Nonclimatic trends are very small and represent random noise that can be removed by averaging. If the same data are analyzed using the more conventional approach of aligning the series by ring number and fitting a regression line, so that the magnitude of the age trend is based on the slope of the mean and the statistical significance on the correlation coefficient, the results are very different. We demonstrate that this conventional approach regularly produces spurious age trends with grossly inflated probabilities, because of offsets in the mean values of series of different length. We conclude that there is no need to detrend stable oxygen isotope series from individual trees or timbers of oak from the UK and that to do so would remove important climatic information. Long isotope chronologies can safely be constructed by combining data from multiple individual trees, or by pooling material from trees prior to chemical treatment and isotopic measurement. Age‐related trends may occur in other species or in other regions, but where they have been identified using the conventional "slope of the mean" approach they should be reassessed using the "mean of the slope" approach. Key Points: No age‐related trends are found in stable isotopes from oak tree rings based on a case study in the UK The conventional method of trend identification can produce spurious age trends with grossly inflated probabilities Age‐related trends may occur in other species or in other regions, but should be reassessed using the "mean of the slope" approach